2021
DOI: 10.1523/eneuro.0315-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Putting Together Pieces of the Lateral Septum: Multifaceted Functions and Its Neural Pathways

Abstract: The lateral septum (LS) is implicated as a hub that regulates a variety of affects, such as reward, feeding, anxiety, fear, sociability, and memory. However, it remains unclear how the LS, previously treated as a structure of homogeneity, exhibits such multifaceted functions. Emerging evidence suggests that different functions of the LS are mediated largely by its diverse input and output connections. It has also become clear that the LS is a heterogeneous region, where its dorsal and ventral poles play dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 92 publications
(200 reference statements)
2
73
0
Order By: Relevance
“…The LS is implicated in several social behaviors and plays a critical role in how animals assess and respond to social contexts (Sheehan et al, 2004 ). The LS acts as a gating mechanism to control several emotion regulation processes, such as reward, anxiety, sociability, and memory (Sheehan et al, 2004 ; Rizzi-Wise and Wang, 2021 ). Among these behaviors, the LS is particularly important for social approach.…”
Section: Discussionmentioning
confidence: 99%
“…The LS is implicated in several social behaviors and plays a critical role in how animals assess and respond to social contexts (Sheehan et al, 2004 ). The LS acts as a gating mechanism to control several emotion regulation processes, such as reward, anxiety, sociability, and memory (Sheehan et al, 2004 ; Rizzi-Wise and Wang, 2021 ). Among these behaviors, the LS is particularly important for social approach.…”
Section: Discussionmentioning
confidence: 99%
“…The core nodes for controls are putative homologs of the pre-optic area (PM, Ppa l ) and the lateral septum (Vv a ) in mammals (O’Connell and Hofmann, 2011 ) suggesting activity in the SDMN in the absence of social stimuli that engages salience monitoring in the environment, through the lateral septum (Rizzi-Wise and Wang, 2021 ) linked to the regulation of internal states, through the pre-optic area.…”
Section: Discussionmentioning
confidence: 99%
“…Although no circuit involving the LS has yet been identified that exerts this inhibitory effect on this pathway, this does not exclude this as a possibility. This is particularly since emerging evidence suggests that LS may be divided into functionally distinct subregions (see Rizzi‐Wise & Wang, 2021 for a review) and multiple regions may feed into this and other similar circuits.…”
Section: Discussionmentioning
confidence: 99%